INCREASE OF AVERAGE ENERGY BY THE PROCESS OF MEASUREMENT - Daboul, J. (Editions Physique, 1992)
A paradox is pointed out and resolved by proving that the average energy E = [H] of a macroscopic system in thermal equilibrium must increase by the measurement of an observable A which does not commute with the Hamiltonian H. The proof follows as a corollary of a more general result, which states that under certain conditions the expectation value [C] of an observable C should increase by the measurement of another observable A, if [A, C] not-equal 0.